Heat treatment of quinoa (Chenopodium quinoa Willd.) albumin: Effect on structural, functional, and in vitro digestion properties - Yang, Chao; Zhu, Xijin; Zhang, Zhaoyun; Yang, Farong; Wei, Yuming; Zhang, Zhen; Yang, Fumin (Frontiers in Nutrition, 2022)
Quinoa seeds are rich in protein, polyphenols, phytosterols, and flavonoid substances, and excellent amino acid balance that has been revisited recently as a new food material showing potential applied in fitness and disease prevention. Heat treatment is one of the most effective strategies for improving the physiochemical characteristics of a protein. However, research examining the effects of temperature on quinoa albumin (QA) properties is limited. In this study, QA was subjected to thermal treatment (50, 60, 70, 80, 90, 100, and 121°C). SDS−PAGE revealed that QA is composed of several polypeptides in the 10−40 kDa range. Amino acid (AA) analysis showed that the branched-chain amino acids (BCAAs), negatively charged amino acid residues (NCAAs), and positively charged amino acids (PCAAs) contents of QA were more than double that of the FAO/WHO reference standard. Additionally, heating induced structural changes, including sulfhydryl-disulfide interchange and the exposure of hydrophobic groups. Scanning electron microscopy demonstrated that the albumin underwent denaturation, dissociation, and aggregation during heating. Moreover, moderate heat treatment (60, 70, and 80°C) remarkably improved the functional properties of QA, enhancing its solubility, water (oil) holding capacity, and emulsification and foaming characteristics. However, heating also reduced the in vitro digestibility of QA. Together, these results indicate that heat treatment can improve the structural and functional properties of QA. This information has important implications for optimizing quinoa protein production, and various products related to quinoa protein could be developed. which provides the gist of commercial applications of quinoa seeds for spreading out in the marketplace.